(untitled) (CIPEEX, 2023)
IT IS KNOWN THAT SUSTAINABILITY IS A TOPIC DISCUSSED WORLDWIDE DUE TO THE HARMFUL WAY OF LIFE THAT HUMANITY HAS ADOPTED. THEREFORE, ENVIRONMENTAL EDUCATION CAN BE A FUNDAMENTAL TOOL IN THIS CONTEXT, CAPABLE OF BALANCING SUSTAINABLE DEVELOPMENT. THEREFORE, INCLUDING THIS TOPIC IN BASIC EDUCATION SCHOOL UNITS THROUGH RESPONSIBLE PRACTICES IS ESSENTIAL FOR THE FORMATION OF CITIZENS SENSITIVE TO UNDERSTANDING THE FRAGILE BALANCE OF THE BIOSPHERE. THUS, THE MAIN OBJECTIVE OF THIS RESEARCH IS TO RAISE AWARENESS AMONG STUDENTS AT A PUBLIC SCHOOL ON THE OUTSKIRTS OF ANÁPOLIS - GO ABOUT THE IMPORTANCE OF PRESERVING THE ENVIRONMENT FOR FUTURE GENERATIONS. THROUGH LECTURES AND THE IMPLEMENTATION OF A COMPOSTING SYSTEM AT SCHOOL, STUDENTS WILL HAVE THE OPPORTUNITY TO LEARN ABOUT THE ORGANIC WASTE CYCLE AND LEARN HOW TO TRANSFORM ORGANIC WASTE INTO BENEFITS, STRENGTHENING SUSTAINABLE PRACTICES.